The Effect of Digital Zakat and Accounting on Corporate Sustainability Through Financial Transparency - Abdul Razzak Alshehadeh; Murad Ali Ahmad Al-Zaqeba; Ghaleb Awad Elrefae; Haneen Aqel Al-Khawaja; Nader Mohammad Aljawarneh (AESS Publications, 2024)
Indexed by Scopus